2021
DOI: 10.1620/tjem.255.61
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak in Italy: Report on the First 124 Consecutive Patients Treated at Home

Abstract: North Italy emerged as an epicenter of COVID-19 in the Western world. The majority of studies of patients with COVID-19 have focused on hospitalized patients, and data on early outpatient treatment are limited. This research retrospectively examines consecutive symptomatic adults who did not present to a hospital but who experience laboratory confirmed (nasopharyngeal swabs) or probable COVID-19 infection. From March 12 to April 12, 2020, 124 consecutive patients with laboratory-confirmed COVID-19 infection (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…COVID-19 is a multisystemic disease that involves hyperinflammation and hypercoagulation, which are closely connected to each other. Based on these pathophysiological mechanisms of the disease, various multidrug approaches were proposed for early outpatient treatment of mild COVID-19 [ 3 , 4 , 6 , 7 ]. Nonsteroidal anti-inflammatory drugs (NSAIDs) administered at the beginning of the symptoms have shown to significantly reduce hospitalization and disease duration in observational studies [ 3 - 5 , 9 ] and in a small open-label RCT [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 is a multisystemic disease that involves hyperinflammation and hypercoagulation, which are closely connected to each other. Based on these pathophysiological mechanisms of the disease, various multidrug approaches were proposed for early outpatient treatment of mild COVID-19 [ 3 , 4 , 6 , 7 ]. Nonsteroidal anti-inflammatory drugs (NSAIDs) administered at the beginning of the symptoms have shown to significantly reduce hospitalization and disease duration in observational studies [ 3 - 5 , 9 ] and in a small open-label RCT [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, many general practitioners (GPs) considered it unethical to neglect any intervention based on safe therapies following relevant pathophysiological rationales, especially in very old people [ 3 ]. Observational studies showed that early home treatment with nonsteroidal anti-inflammatory drugs (NSAIDs), possibly associated with vitamins and micronutrients, is effective in reducing hospitalization and symptom duration [ 3 - 5 ], and that’s why some multidrug approaches were proposed [ 3 , 4 , 6 , 7 ]. At the very beginning of the worldwide pandemic outbreak, in Italy, healthcare professionals had to face such a new and aggressive disease that some of them created voluntary groups of doctors aiming to discuss the possible best scientific evidence for a helpful therapy, thus developing shared and efficient schemes of early therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The development lifecycle followed an iterative, agile methodology through weekly development cycles and active feedback from stakeholders. [20] The primary software management tool used was Jira (Atlassian, Sidney, Australia) which stored tickets, documentation, and connected to the codebase.…”
Section: Patient Monitoring and Clinical Workflowmentioning
confidence: 99%